Severe psoriasis in a 3-year-old child treated with methotrexate. - Baswedan, R.; Hidayati, A.N.; Widia, Y.; Sawitri; Suyoso, S. (European Journal of Pediatric Dermatology, 2026)
Psoriasis vulgaris in early childhood is uncommon and may present diagnostic challenges, particularly when clinical features mimic other inflammatory dermatoses. We report a 3-year-old boy with widespread erythematous, scaly plaques involving the scalp, face, trunk, extremities, and inguinal region, accompanied by obesity as a relevant comorbidity. Histopathological examination confirmed psoriasis vulgaris, and methotrexate was initiated at 0.3 mg/kg/week with folic acid supplementation. Progressive clinical improvement was observed within the first month, and near-complete resolution of lesions occurred after two months, without adverse effects or laboratory abnormalities. This case highlights methotrexate as an effective and well-tolerated systemic option for moderate-to-severe pediatric psoriasis, particularly in resource-limited settings or when comorbid obesity is present.